2016
DOI: 10.1186/s12878-016-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Sickle-cell disease in febrile children living in a rural village of Madagascar and association with malaria and respiratory infections

Abstract: BackgroundIn Madagascar, the last study on sickle cell disease (SCD) was done in the early 1980s. The country is known as endemic for malaria and respiratory infections. The main objective of this study was to estimate the prevalence of SCD; the secondary objective was to evaluate its association with malaria and respiratory infections.MethodsThis is a cross-sectional study which was carried out in a rural village in the south east coast of Madagascar between May 2011 and November 2013. Participants were child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
0
2
Order By: Relevance
“…Univariate and multivariate regression analysis of the risk of having malaria in symptomatic participants showed that HIV status and sickling status did not cause any significant increase or decrease in risk, even though 14.4 and 17.7% of participants carried the HbS allele and had HIV respectively. In this study neither HbSS nor HbAC showed any influence on malaria; other studies have also been unable to show a clear relationship between them [ 16 , 18 , 36 ]. Whilst certain studies have shown decreased risk for malaria in people with HbSS [ 37 , 38 ], others have shown no difference between HbSS allele and HbAA where malaria risk is concerned [ 16 , 18 , 36 ].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Univariate and multivariate regression analysis of the risk of having malaria in symptomatic participants showed that HIV status and sickling status did not cause any significant increase or decrease in risk, even though 14.4 and 17.7% of participants carried the HbS allele and had HIV respectively. In this study neither HbSS nor HbAC showed any influence on malaria; other studies have also been unable to show a clear relationship between them [ 16 , 18 , 36 ]. Whilst certain studies have shown decreased risk for malaria in people with HbSS [ 37 , 38 ], others have shown no difference between HbSS allele and HbAA where malaria risk is concerned [ 16 , 18 , 36 ].…”
Section: Discussioncontrasting
confidence: 97%
“…In this study neither HbSS nor HbAC showed any influence on malaria; other studies have also been unable to show a clear relationship between them [ 16 , 18 , 36 ]. Whilst certain studies have shown decreased risk for malaria in people with HbSS [ 37 , 38 ], others have shown no difference between HbSS allele and HbAA where malaria risk is concerned [ 16 , 18 , 36 ]. Also, heterozygous HbAC has not been found to influence malaria in some studies [ 16 ], yet some studies have shown malaria to be reduced in people with HbAC [ 23 ].…”
Section: Discussioncontrasting
confidence: 97%